2021
DOI: 10.1002/bmc.5214
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of bioactive constituents and pharmacological activities from different parts of Nauclea officinalis

Abstract: The stems of Nauclea officinalis have been utilized as a crude drug in China, so other parts of the plant are abandoned, resulting in a waste of traditional Chinese medicine resources. To determine the distribution and content of the alkaloids, phenolic acids and iridoid in different organs (stem, branch, leaf and bark) of this plant, a reliable method has been established using LC-MS/MS. Nine constituents, namely strictosamide, vincosamide, chlorogenic acid, sweroside, naucleamide B, protocatechuic acid, pumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Monoterpene indolic alkaloid (N-β-glucopyranosyl vincosamide) is the main component of extracts from the leaves of Psychotria leiocarpa, which is found in tropical and subtropical regions. Many studies have shown that Vinco has anti-inflammatory activities in vivo and anti-proliferative effects in vitro [1,7,[24][25][26]; and Vinco also has cytotoxic, anthelmintic, analgesic, anti-bactericidal activities [2,[27][28][29] and with potential therapeutic effects on type 2 diabetes [30]. Evidence indicated Vinco as protective agent in cardiac damage and vascular dysfunction [31].…”
Section: Discussionmentioning
confidence: 99%
“…Monoterpene indolic alkaloid (N-β-glucopyranosyl vincosamide) is the main component of extracts from the leaves of Psychotria leiocarpa, which is found in tropical and subtropical regions. Many studies have shown that Vinco has anti-inflammatory activities in vivo and anti-proliferative effects in vitro [1,7,[24][25][26]; and Vinco also has cytotoxic, anthelmintic, analgesic, anti-bactericidal activities [2,[27][28][29] and with potential therapeutic effects on type 2 diabetes [30]. Evidence indicated Vinco as protective agent in cardiac damage and vascular dysfunction [31].…”
Section: Discussionmentioning
confidence: 99%
“…ex Pitard, is one of the most commonly used traditional medicines in China and is mainly distributed in Hainan, Guangxi, Guangdong, and other provinces in the south of China [1]. Modern pharmacological studies reported that Nauclea ofcinalis exhibits various biological properties such as antibacterial, anti-infammatory, and analgesic activity [2][3][4][5][6]. As a traditional Chinese medicine, the stems and twigs of Nauclea ofcinalis are used for the treatment of colds, fever, acute tonsillitis, sore throat, and other diseases [1,7].…”
Section: Introductionmentioning
confidence: 99%